Probabilistic stability analysis of an earth dam by Stochastic Finite Element Method based on field data. (September 2018) - Mouyeaux, A.; Carvajal, C.; Bressolette, P.; Peyras, L.; Breul, P.; Bacconnet, C.
Abstract: This paper performs a probabilistic stability analysis for an existing earthfill dam using a Stochastic Finite Element Method (SFEM) and considering the spatial variability of soil properties based on field data. Previous works on probabilistic slope stability analysis are generally based on hypothetical data while using data from existing earth structures is not widespread. A probabilistic procedure based on field data is here implemented to analyze the stability of an existing embankment dam. The spatial variability of several soil properties is modeled from the geostatistical analysis of the available dataset of the dam studied. Random variables and random fields representing the variability of dam materials are integrated into an FE model by performing Monte Carlo simulations (MCS). This probabilistic analysis based on field data allowed to characterize the variability of the sliding safety factor for the case study of an existing dam.